EUROMOD baseline report - Sofía Maier; Mattia Ricci (European Commission, Joint Research Centre (JRC), 2022)
This paper presents baseline results from the latest public version (I4.0+) of EUROMOD, the tax-benefit microsimulation model for the EU. We begin by briefly discussing the process of updating EUROMOD. We then present indicators for income inequality and at-risk-of-poverty using EUROMOD and discuss the main reasons for the differences between these and their correspondent from the EU Statistics on Incomes and Living Conditions (EU-SILC). We further compare EUROMOD distributional indicators across all EU 27 countries and over time between 2018 and 2021. Finally, we provide estimates of marginal effective tax rates (METR), an indicator which captures the effect of tax-benefit systems on work incentives at the intensive margin. Throughout the paper, we highlight both the potential of EUROMOD as a tool for policy analysis and the caveats that should be borne in mind when using it and interpreting results.
Keywords: H24; H53; I32; I38; 330; taxes; benefits; inequality; poverty; EUROMOD